2022
DOI: 10.3390/bioengineering9090424
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Design Method of Gradient Porous Structure for Stabilized and Lightweight Mandibular Prosthesis

Abstract: Compared to conventional prostheses with homogenous structures, a stress-optimized functionally gradient prosthesis will better adapt to the host bone due to its mechanical and biological advantages. Therefore, this study aimed to investigate the damage resistance of four regular lattice scaffolds and proposed a new gradient algorithm for stabilized and lightweight mandibular prostheses. Scaffolds with four configurations (regular hexahedron, regular octahedron, rhombic dodecahedron, and body-centered cubic) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The results showed a strong correlation between lattice topology and load transmission capacity, while mechanical failure strongly depends on the strut size and configuration; moreover, the computational model results indicated that the optimized scaffold can provide an excellent mechanical environment for bone regeneration. Liu et al [ 130 ] compared conventional prostheses with homogeneous structures to stress-optimized functionally graded devices. They investigated, in silico, the damage resistance of four scaffolds and proposed a novel gradient algorithm for lightweight mandibular devices.…”
Section: Biomedical Device Case Studiesmentioning
confidence: 99%
“…The results showed a strong correlation between lattice topology and load transmission capacity, while mechanical failure strongly depends on the strut size and configuration; moreover, the computational model results indicated that the optimized scaffold can provide an excellent mechanical environment for bone regeneration. Liu et al [ 130 ] compared conventional prostheses with homogeneous structures to stress-optimized functionally graded devices. They investigated, in silico, the damage resistance of four scaffolds and proposed a novel gradient algorithm for lightweight mandibular devices.…”
Section: Biomedical Device Case Studiesmentioning
confidence: 99%
“…Altering the microstructure of the titanium also has implications for the success of the computation model. Through introductions of scaffolding such as tetrahedral or with varying pore and strut size, the models are more customizable [74,80]. These studies answer questions related to the success of changing the material properties of titanium to create more favourable models in relation to mastication and force distributions.…”
Section: ) Prosthetic Designmentioning
confidence: 99%
“…A press-fit implant is cementless and has porous features that allow biological fixation, which is important for young active patients. In a recent investigation [12], damage resistance of suggested four lattice structures (regular hexahedron, regular octahedron, rhombic dodecahedron, and body-centered cubic), was studied using gradient algorithm for stabilized and lightweight mandibular prostheses. The introduced algorithm was aided by finite element analysis to select an optimal lattice structure.…”
Section: Introductionmentioning
confidence: 99%